2017
DOI: 10.21109/kesmas.v11i3.1262
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of National Health Insurance Policy to the Implementation of Health Promotion Program on Public Health Center in Indonesia

Abstract: The National Health Insurance (NHI) Program was implemented in Indonesia on January 1 st 2014. This program definitely brings some changes into managerial aspect in public health center (PHC). This study aimed to determine an impact of NHI policy in the implementation of health promotion programs at PHC in South Tangerang City, Indonesia. This study was conducted using qualitative method during February and March 2016. The impact of NHI is seen on policy, budget, equipment, human resource and implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
1
3
0
1
Order By: Relevance
“…This study reveals that the improvement of budget received by PHC has led to the improved implementation of Individual Health Program and Public Health Program, particularly the essential Public Health Program. The finding is in line with the result of a study by Nurmansyah & Kilic, 12 that showed the improved revenue from capitation fund of NHI has improved health promotion activities of PHC in South Tangerang City. However, in line with the findings of other studies, improvement of budget does not necessarily result in an increase in financial support for all PHC programs.…”
Section: Discussionsupporting
confidence: 89%
“…This study reveals that the improvement of budget received by PHC has led to the improved implementation of Individual Health Program and Public Health Program, particularly the essential Public Health Program. The finding is in line with the result of a study by Nurmansyah & Kilic, 12 that showed the improved revenue from capitation fund of NHI has improved health promotion activities of PHC in South Tangerang City. However, in line with the findings of other studies, improvement of budget does not necessarily result in an increase in financial support for all PHC programs.…”
Section: Discussionsupporting
confidence: 89%
“…Policy for the deliberate sensitization of the elderly to register for coverage with incentives such as comprehensive differential care may help raise the coverage rates for the elderly. In Indonesia for example, SHI has been used to fund health promotion programs targeted at people with chronic illnesses 24 as they are prone to treatment fatigue over time 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Pembiayaan kesehatan merupakan aspek penting yang sangat mendukung jalannya roda pelayanan kesehatan untuk masyarakat. Secara umum, pembiayaan kesehatan dapat ditanggung oleh pemerintah, asuransi agensi swasta, atau biaya mandiri (Blumel et al, 2020;Nurmansyah & Kilic, 2017). Meskipun terdapat beberapa skema pembiayaan kesehatan, tetapi tidak dapat dipungkiri bahwa skema utama yang menanggung beban kesehatan banyak masyarakat adalah pembiayaan dan asuransi dari pemerintah (Erlangga et al, 2019).…”
Section: Pendahuluanunclassified